Latent profile analysis of passion for work and its relationship with psychological well-being - Karolina Mudło-Głagolska (Nofer Institute of Occupational Medicine, 2022)
Background So far, studies based on the dualistic model of passion have ignored how the 2 different types of passion interact in a person's identity. The aim of this article is to identify profiles of passion for work and their consequences for psychological well-being. Material and Methods The survey was conducted on a sample of 522 employees of various employment sectors. The Passion Scale was used to assess passion for work, while to explore well-being, the anxiety and depression subscale of the General Health Questionnaire (GHQ-28) and the Subjective Vitality Scale were employed. Latent profile analysis (LPA) was used to distinguish the passion profiles, following which the results regarding well-being in the following groups were compared using non-parametric tests. Results Four passion profiles have been identified. They are termed as high-moderate (profile 1: high harmonious passion for work and moderate obsessive passion for work), high (profile 2: high harmonious passion for work and obsessive passion for work), optimal (profile 3: high harmonious passion for work and low obsessive passion for work), and low (profile 4: low harmonious passion for work and low obsessive passion for work). Employees with a low score for both harmonious passion for work and obsessive passion for work had the lowest score regarding well-being. Conclusions This study was one of the first to use the LPA approach to explore the configuration of passion for work. It provided an indication of how the different dimensions and levels of passion set up with each other and what their consequences would be. The conducted research emphasized the protective role of the harmonious passion for work against the negative effect of obsessive passion for work. Med Pr. 2022;73(4):315-23